Phosphene Attributes Depend on Frequency and Intensity of Retinal tACS - Kvašňák, Eugen; Orendáčová, Mária; Vránová, Jana (Physiological research, 2022)
Phosphene is the experience of light without natural visual stimulation. It can be induced by electrical stimulation of the retina, optic nerve or cortex. Induction of phosphenes can be potentially used in assistive devices for the blind. Analysis of phosphene might be beneficial for practical reasons such as adjustment of transcranial alternating current stimulation (tACS) frequency and intensity to eliminate phosphene perception (e.g., tACS studies using verum tACS group and sham group) or, on the contrary, to maximize perception of phosphenes in order to be more able to study their dynamics. In this study, subjective reports of 50 healthy subjects exposed to different intensities of retinal tACS at 4 different frequencies (6, 10, 20 and 40 Hz) were analyzed. The effectiveness of different tACS frequencies in inducing phosphenes was at least 92 %. Subject reported 41 different phosphene types; the most common were light flashes and light circles. Changing the intensity of stimulation often induced a change in phosphene attributes. Up to nine phosphene attributes changed when the tACS intensity was changed. Significant positive correlation was observed between number of a different phosphene types and tACS frequency. Based on these findings, it can be concluded that tACS is effective in eliciting phosphenes whose type and attributes change depending on the frequency and intensity of tACS. The presented results open new questions for future research.
Keywords: Phosphenes; Photic Stimulation; Transcranial Direct Current Stimulation; retina; lidé; Visual Cortex; fosfeny; přímá transkraniální stimulace mozku; světelná stimulace; Retina; zrakové korové centrum; Humans